El Liderazgo Emocional Y Su Repercusión En Las Instituciones Educativas Españolas - Costela, Vanesa Román; Lucena, Juan Ruiz (European Scientific Journal, ESJ, 2016)
This article presents a theoretical review based in one of the emerging new leadership models: emotional leadership; likewise, the impact of exercising this style of leadership in Spanish educational institutions. These effects are in the areas of education, the physical and mental health of members of the educational community, improved interpersonal relationships, avoidance of stress and job anxiety. Finally, it will conclude with the importance of including Emotional Intelligence in training programs for headmasters through coaching, to emphasize the importance of exercising an emotional leadership style as a means of improving the organization and quality of Spanish schools.